Basophils, a neglected minority in the immune system, have come into the limelight at last. (2nd May 2021) - Karasuyama, Hajime; Shibata, Sho; Yoshikawa, Soichiro; Miyake, Kensuke
Abstract: Basophils, the rarest granulocytes, were identified by Paul Ehrlich more than 140 years ago, much earlier than the discovery of T and B cells. Unfortunately, basophils were often mixed up with tissue-resident mast cells because of some phenotypic similarities between them and considered erroneously as minor relatives or blood-circulating precursors of mast cells. Moreover, basophil research was hindered by the rarity of basophils and the paucity of useful analytical tools, and therefore basophils had often been neglected in immunological studies. A series of studies using newly developed tools, including basophil-depleting antibodies and genetically engineered mice deficient only in basophils, have clearly defined previously unrecognized roles of basophils, that are distinct from those played by tissue-resident mast cells. In this mini-review, we highlight recent advances in our understanding of basophil functions, particularly focusing on their roles in the regulation of innate and acquired immunity, allergic reactions, autoimmunity and protective immunity against parasitic infections, mainly based on animal studies. Further studies on human basophils would facilitate the development of new strategies for the treatment of basophil-associated disorders.